Weight-Related Information Avoidance Prospectively Predicts Poorer Self-Monitoring and Engagement in a Behavioral Weight Loss Intervention. Issue 2 (3rd June 2020) - Schumacher, Leah M; Martinelli, Mary K; Convertino, Alexandra D; Forman, Evan M; Butryn, Meghan L
Abstract: Background: Self-monitoring is a key component of behavioral weight loss (BWL) interventions. Past research suggests that individuals may avoid self-monitoring in certain contexts (e.g., skipping self-weighing after higher-than-usual calorie intake). However, no studies have attempted to quantify individuals' inclination to avoid information about their weight control ("weight-related information avoidance"; WIA) or prospectively examined its implications for treatment engagement and outcomes in BWL programs. Purpose: Characterize WIA using a validated questionnaire among adults enrolled in BWL treatment and examine whether WIA prospectively predicts self-monitoring adherence, session attendance, treatment discontinuation, or weight loss. Methods: Participants ( N = 87; M BMI = 34.9 kg/m 2, 83% female) completed a measure of WIA prior to starting a 12 week, group-based BWL intervention. Participants were given digital self-monitoring tools and instructed to self-monitor their food intake daily, physical activity daily, and body weight weekly (Weeks 1–10) and then daily (Weeks 11–12). Session attendance and treatment discontinuation were recorded. Weight was measured in-clinic pretreatment and posttreatment. Results: While mean WIA was low ( M = 2.23, standard deviation [ SD ] = 0.95; potential scale range: 1–7), greater WIA predicted poorer attendance ( r = − .23; p = .03) and poorer self-monitoring of physical activity ( r = −.28; p = .009) and body weight ( r = −.32; p = .003). WIA did not predict food monitoring ( p = .08), treatment discontinuation ( p = .09), or 12 week weight loss ( p = .91). Conclusions: Greater WIA, as assessed via a brief questionnaire, may place individuals at risk for poorer self-monitoring and treatment engagement during BWL. Further research on the implications of WIA in the context of weight management is warranted, including evaluation of correlates, moderators, and mechanisms of action of WIA. Clinical Trial Registration: NCT03337139. Abstract : Adults in a behavioral weight loss program who scored higher on a pre-treatment questionnaire assessing their inclination to avoid information about their weight control attended fewer treatment sessions, self-weighed less often, and self-monitored physical activity less frequently during a 12-week intervention.